Combination Therapy of Pulsed Dye Laser With Intense Pulsed Light in Port-Wine Stain Treatment: A Prospective Side-by-Side Comparison. Issue 9 (31st May 2021) - Yu, Wenxin; Cen, Qingqing; Chen, Yanyu; Zhu, Jiafang; Lin, Xiaoxi
Abstract : BACKGROUND: Pulsed dye laser (PDL) treatment currently represents the mainstream choice for port-wine stain (PWS) treatment in accordance with selective photothermolysis. However, most PWS lesions cannot be removed despite several treatments. Intense pulsed light (IPL) is reportedly an effective alternative to PDL for PWS treatment. No studies have thus far been reported on the combination therapy of PDL with IPL in PWS treatment. OBJECTIVE: This study evaluated the efficacy and safety of PDL with IPL for PWS treatment. METHODS: A total of 33 PWS lesions underwent 3 treatment sessions. Each PWS was divided into IPL + PDL, PDL, and untreated sites. Therapeutic outcomes were evaluated by visual assessment and chromametric assessment 3 months after the final treatment. RESULTS: The overall average blanching rates were 36.2% and 32.6% at the sites treated with IPL + PDL and PDL, respectively ( p > .05). No permanent side effects were reported. CONCLUSION: In this laser setting, although IPL + PDL is a safe and effective PWS treatment, no significant improvement in the efficacy was observed using IPL + PDL in contrast to PDL alone.